Ẽmin ẽg mỹ há - Caminhos de bem viver: projetos-de-vida das Tytãg e Kyrũ Kanhgág (Kaingang) na comunidade Por Fi Ga em São Leopoldo-RS - Amorim, Gabriel Chaves (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation is presented in the form of a ‘basket’ on the life projects of the youths of the Por Fi Ga indigenous community, in the city of São Leopoldo, Brazil. As a result, we theorize that individual projects converge in the production of common subjectivities. This embracing project-of-community refers to values of organization of community and economic life, through the rãnhrãj/work with the régre/relatives. In the agriculture and crafts, indigenous youth emancipate themselves and build themselves as subjects. To reach such definition, twenty (20) ethnographic moments were carried out, systematized, transcribed and ‘woven’ together with social theory. The (ethno)methodology “jykre tãn/owner of knowledge” analyzes the meaning of sociological categories but based on kanhgág cosmology. This vafy/braiding of south-epistemological theories is intended to promote cognitive justice, ecology of knowledge and emancipatory emergences.
Keywords: Kaingang; Projetos de vida; Economia social solidária; Emancipação; Ecologia dos saberes; Life projects; Social and solidarity economy; Emancipation; Ecology of knowledge; ACCNPQ::Ciências Humanas::Sociologia